Psychometric properties of career aspirations scale among undergraduate students - Mhule, Daliko; Sumbizi, Enerico J.; Ngonyani, Mussa (UIN Maulana Malik Ibrahim Malang, 2025)
Career aspiration is essential for individual’s preparation and role identity development for future responsibility in society. However, development and validation of scales for assessing career aspirations in Tanzanian context, particularly in higher education institutions is limited. The present study aimed at assessing the psychometric properties of the revised career aspiration scale (CAS-R) (O’Brien Gregor, 2016) among undergraduate students in Tanzania. The study employed cross-sectional research in which a quantitative approach was adopted. The study conveniently sampled 231 undergraduate students from Mbeya University of science and Technology to participate in the study. Among the participants; 129(55.8%) males and 102(44.2%) females (MAge=22 years, SD=1.84). Data analysis involved descriptive analysis and confirmatory factor analysis (CFA) using IBM SPSS and AMOS version 23. The CFA yielded retained the three-factor model comprising achievement aspiration, leadership aspiration and educational aspiration consisting of 24 scale items in total. The model showed good model fit: X2/df= 1.89, CFI=0.94, TLI=0.93, RMSEA=0.062, SRMR=0.062. The measurement model demonstrated reasonable convergence and discriminant validity. The composite of the sub-scales showed adequate internal consistency of above the threshold value (α0.7). The study’s findings revealed that the final three-factor model of the validated revised career aspiration scale is valid and reliability for assessing the career aspirations among undergraduate students in higher learning institutions in Tanzania.